Fluid Management in Critically Ill Patients with Acute Kidney Injury: Role of Noninvasive Assessment of Stroke Volume - Hassan Effat; Ihab Abdelrahman Alsayed; Rania Alhusseiny; Waleed Farouk (Egyptian Journal of Critical Care Medicine)
Abstract Introduction Acute kidney injury (AKI) occurs in up to 50% of patients admitted to the intensive care units. Optimization of volume status is a challenging step in management of AKI patients. We tried to validate a new protocol for assessment of fluid responsiveness and guiding fluid therapy in critically ill patients with AKI. Materials and Methods This study was conducted on 40 critically ill patients with AKI. Patients were randomly divided into 2 groups: group A; volume status was optimized by central venous pressure (CVP)/ACVP and group B; volume status was optimized by passive leg raising (PLR) and fluid challenge induced stroke volume variation (SVV) using echocardiography. Both groups were compared regarding outcome. Results No significant difference in both groups regarding any of the baseline characteristics. Group A received more fluids compared to group B after 48hours (3.7±0.7 versus 2.2±0.6 L, respectively, P<.001). This was associated with increased morbidity and mortality. In group A, the need for mechanical ventilation (MV) was higher (P .048), the duration of MV was longer (P .04) with larger number of patients failed weaning (P .036). The need for vasopressors was higher in group A (P .019) with more patients in need for RRT compared to group B, but it did not reach statistical significance (P .2). No difference between the two groups regarding the length of intensive care unit stay (12.10±11.83days in group A versus 6.35±3.86 group B, P .183). However, the mortality rate was higher in group A (40%) compared to group B (10%), P .028. Discussion The use of SVV for guiding fluid therapy in AKI patients was associated with less fluid intake, less morbidly and mortality compared to CVP/ACVP.